Estrategias de la economía circular en la cooperativa de producción pesquera artesanal “odisea - Cedeño Gómez, Joseph Jordan (2023)
This research focuses on the "Circular Economy Strategies" in the Artisanal Fishing Production Cooperative "Odisea" located in Canton Mocache. Its main objective is to propose effective strategies for the cooperative, optimizing its production process, reducing its environmental impact and promoting long-term sustainability. To achieve this result, the cooperative's current production process was analyzed, showing it in flow diagrams by stages and a general flow chart. Subsequently, the project identified all the possible strategies of circular economy that are necessary for the cooperative, extracting first with a SIPOC diagram, then a process management map was made as a proposal for the use of circular economy in the cooperative. As a conclusion we have the focus on the elaboration of a detailed proposal of the effective circular economy strategy for the cooperative "Odisea", which was developed with the Deming cycle method.